Analysis on the Time-Varying Fragility of Offshore Concrete Bridge. (20th January 2019) - Liang, Yan; Yan, Jia-lei; Wang, Jun-lei; Zhang, Peng; He, Bao-jie
Abstract : For offshore bridges, the most prominent problem in the whole life cycle is that it is in an earthquake prone zone and an offshore corrosion environment at the same time. A nonlinear dynamic analysis model is set up for an offshore multispan and continuous rigid frame bridge based on the OpenSEES platform. The fragility surface of the bridge pier, bearing, bridge platform, and system are established by selecting a reasonable damage constitutive model of the material durability and a damage index analysis that studies the damage of the bridge durability to time-varying seismic fragility of bridge components and the system of the whole life cycle in offshore environment. The results show that the durability damage will lead to a constant decline in seismic capacity of the pier and an increase of the seismic demand under earthquake action as well as the probability to reach the ultimate failure state; compared to high piers, a low pier is more vulnerable to the offshore corrosion environment; the seismic fragility of bridge platform is higher than that of simply bearing; and the influence of offshore corrosion on environment is relatively large. With the prolongation of service period, the effect of durability damage on the seismic fragility of bridge system cannot be ignored in the coastal environment and it is necessary to make a reasonable evaluation on the seismic fragility of bridge structure during the whole life period.